Sosialisasi Dampak Pernikahan Usia Dini terhadap Keharmonisan Rumah Tangga pada Remaja di Desa Mlandangan Kecamatan Pace Kabupaten Nganjuk - Abdul Hafidz Miftahuddin; Muhammad Shinwanuddin; M. Munir (LP3M STAI Darussalam Krempyang Nganjuk, 2022)
Early marriage is a marriage performed at an age below the productive age (over 19 years). Early marriage can have various impacts on family harmony due to a lack of physical and psychological preparation to form a sakinah family. This assumption arises because of the lack of knowledge from the community about the importance of education for adolescents. This program is implemented using a participatory approach. The facilitation steps are as follows: 1. Social analysis, 2. Programming, 3. Coordination, 4. Implementation, 5. Control. In the socialization seminar on understanding the impact of early marriage, service partners namely IPNU & IPPNU were given guidelines on the impact of early marriage, and could also consult with community leaders who had a better understanding of the impact of marriage at an early age. early age. Given the high rate of early marriage, of course many problems are faced by both men and women. Therefore, socialization about marriage at an early age needs to be further encouraged in various parties, including: Adolescents who have not reached the age of 19, both boys and girls and their parents.